The effect of BaF2 concentration and particle size distribution on the luminescence efficiency of YAG:Ce3+phosphors - Valiev D. T. Damir Talgatovich; Khan (Han) Tao; Stepanov S. A. Sergey Aleksandrovich; Vaganov V. A. Vitalii Andreevich; Paygin V. D. Vladimir Denisovich (2018, 2018)
Title screen